Stochastic ARX Algorithms: a New Look at Related Keys Analysis - Kozlov, Alexander A.; Ivanov, Michael A.; Chugunkov, Ilya V. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2022)
The paper is devoted to the problem of a related keys security analysis of ARX stochastic algorithms. The authors provide a new related key function. A new method to analysis has been developed - non-cyclic analysis. An estimate for the number of cyclic shift operations in such algorithms that are resistant to the non-cyclic analysis has been proved. The application of non-cyclic analysis towards modern stochastic ARX algorithms is considered.